Hydrodifluoromethylation of Alkenes with Difluoroacetic Acid. Issue 26 (24th May 2019) - Meyer, Claudio F.; Hell, Sandrine M.; Misale, Antonio; Trabanco, Andrés A.; Gouverneur, Véronique
Abstract: A facile method for the regioselective hydrodifluoromethylation of alkenes is reported using difluoroacetic acid and phenyliodine(III) diacetate in tetrahydrofuran under visible‐light activation. This metal‐free approach stands out as it uses inexpensive reagents, does not require a photocatalyst, and displays broad functional group tolerance. The procedure is also operationally simple and scalable, and provides access in one step to high‐value building blocks for application in medicinal chemistry. Abstract : Terminal alkenes undergo net hydrodifluoromethylation in the presence of an excess of difluoroacetic acid and phenyliodine(III) diacetate in tetrahydrofuran under visible‐light irradiation ( λ =450 nm). This highly practical procedure telescopes access to biorelevant building blocks that would require multiple synthetic steps applying deoxyfluorination chemistry.